Association of cytokines gene polymorphisms (TNF and IL8) with chronic obstructive pulmonary disease development - G. N. Seitova; Ye. B. Bukreyeva; I. S. Kremis; V. P. Puzyryov (Бюллетень сибирской медицины, 2010)
The association of the tumor necrosis TNF-α –308G/A polymorphism and interleukin-8 genetic IL8 –251А/Т polymorphism with the development of the chronic obstructive lung disease (COLD) in two Tomsk populations (Siberian Tatars and Russians) has been studied. The data on interethnic differences in the structure of COLD susceptibility have been obtained. In Siberian Tatars, the TNF –308G allelic variant plays a role in the COLD development. In Russians, no association of the studied genetic markers with COLD was reveled.